Enterprise architecture design using TOGAF at the health center - Reynaldi Thimotius Abineno; Leonard Marten Doni Ratu (JURNAL TEKNIK INFORMATIKA INOVATIF WIRA WACANA, 2022)
Puskesmas is one of the facilities provided by the government in providing services in the health sector for the community in an effort to improve people's welfare. the assisted manulai II health center is one of the health centers located in the Alak district, Kupang City, East Nusa Tenggara province. the puskesmas has not yet implemented ICT so everything is still done manually. technology and information are developing so fast, to improve services at related health centers it is very important to design and plan enterprise architecture through strategies and developments in the health sector. this study will produce a blueprint as an illustration for its application to the puskesmas.